Clinical variants of pityriasis rosea - Urbina, Francisco (World J Clin Cases, 2017)
Pityriasis rosea (PR) is a common erythemato-squamous dermatosis which almost always, is easily diagnosed. Mostly the disease presents in its classical form. However, clinical dermatology is all about variations and PR is not an exception. Variants of the disease in some cases may be troublesome to diagnose and confuse clinicians. Prompt diagnosis and treatment of the condition becomes necessary to avoid unnecessary investigations. We hereby review and illustrate atypical presentations of the disease, including diverse forms of location and morphology of the lesions, the course of the eruption, and its differential diagnoses.